Skin manifestations in familial heterozygous hypercholesterolemia - Pietroleonardo, Lucia (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2009)
Familial hypercholesterolemia, a form of primary hyperlipoproteinemia, is an autosomal dominant disorder characterized by an increase in serum LDL cholesterol concentrations. Multiple types of xanthomas occur, such as tendinous, tuberous, subperiosteal, and xanthelasma. Intertriginous xanthomas are rare, but if present are pathognomonic in this disorder. We report a patient with multiple xanthomas including the very rare intertriginous variety.
Keywords: Achilles Tendon; Aged; Ahilova tetiva; Arcus Senilis; Atherosclerosis; Complications; Etiology; hiperlipoproteinemija; kožne spremembe; Ksantomatoza; Lok senilni; Pathology; Starostniki; Xanthomatosis